P-STAT6, PU.1, and NF-κB are involved in allergen-induced late-phase airway inflammation in asthma patients. Issue 1 (December 2015) - Hoppenot, Deimante; Malakauskas, Kestutis; Lavinskiene, Simona; Sakalauskas, Raimundas
Abstract Background Previousin vitro and animal studies demonstrated that transcription factors p-STAT6 and PU.1 are required to induce interleukin (IL)-9 secretion by T helper (Th) 9 cells. It is believed that n factor-kappaB (NF-κB) plays a role in eosinophil survival. The importance of these transcription factors in the pathogenesis of allergic asthma (AA) in humans is poorly understood. We evaluated p-STAT6 and PU.1 expression in peripheral blood Th9 cells and NF-κB expression in eosinophils during late-phase airway inflammation in AA patients. Methods Nineteen adults with AA and 14 adult healthy individuals (HI) were examined. Peripheral blood collected 24 h before (baseline) and 24 h after bronchial allergen challenge. CD4+ cells and eosinophils were isolated by high-density gradient centrifugation and magnetic separation. The percentage of Th9 cells and apoptotic eosinophils was estimated by flow cytometry. p-STAT6 and PU.1 expression was expressed as mean fluorescence intensity (MFI) in Th9 cells. NF-κB levels were expressed as MFI in peripheral blood eosinophils. Serum IL-9 and IL-5 levels were determined by enzyme-linked immunosorbent assay. Results At baseline, MFI of p-STAT6 and PU.1 in peripheral blood Th9 cells and MFI of NF-κB in eosinophils and, serum IL-5 and IL-9 levels were greater in AA patients (P < 0.05). Decreased eosinophil apoptosis was seen in the AA group compared with HI (P < 0.05). MFI of p-STAT6, PU.1, and NF-κB and serum levels of IL-5 and IL-9 were increased in the AA group 24 h after challenge compared with baseline (P < 0.05). In the AA group, a correlation between serum IL-9 and Th9 cells (r = 0.7, P = 0.001) and MFI of PU.1 (r = 0.6, P = 0.01) 24 h after bronchial allergen challenge was observed. A correlation between Th9 cells and MFI of p-STAT6 (r = 0.45, P = 0.03) as well as MFI of PU.1 (r = 0.5, P = 0.02) 24 h after challenge was only observed in AA patients. A correlation between the MFI of NF-κB and eosinophil apoptosis was observed in AA patients 24 h before (r = −0.46, P = 0.02) and after (r = −0.5, P = 0.02) challenge. Discussions p-STAT6 and PU.1 may be associated with Th9 cells and IL-9 production, whereas NF-κB and IL-5 may be associated with reduced eosinophil apoptosis in allergen-induced late-phase airway inflammation. Trial registration ClinicalTrials.govNCT02214303